Analysis on Electronic Money Transactions on Velocity of Money in ASEAN-5 Countries - Kartika, Venna Tri; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract. The purpose of this study is to analyze the electronic money transactions on velocity of money in ASEAN-5 countries from 2010 to 2014. For the electronic money, the data used is the volume of transactions. For the gross domestic product and money supply (M1), the data used are currency from each country that has been converted into US dollars. This study uses panel data model, classical assumption test (heteroscedasticity and multicollinearity test), and goodness of fit test (coefficient determination, f test, and t test) to analyze the relationship between electronic money transactions with gross domestic product, money supply (M1), and velocity of money. The results of this study indicate that the volumes of electronic money transactions are increasing in ASEAN-5 countries, while the velocity of money are decreasing. The gross domestic product, money supply (M1), and velocity of money have positive and significant relationships to electronic money transactions for 0.34%, 0.10%, and 0.49% in ASEAN-5 countries. On coefficient of determination test (R2), it shows that 98.41% of dependent variable (electronic money transactions) can be explained by independent variables (gross domestic product, money supply (M1), and velocity of money). Since there is a positive trend in electronic money transactions, the rapid development of non-cash instruments, and a significant relationship between electronic money transactions to GDP, money supply (M1), and velocity of money in all ASEAN-5 countries, including Indonesia, the society should relatively be ready to get into a cashless society.Ã‚Â Keywords: electronic money, GDP, M1, velocity of money, panel data model